A MXene aerogel for hydrogen storage and preparation method thereof

By preparing MXene aerogel for hydrogen storage, the problem of hydrogen storage capacity reduction caused by disordered accumulation in the application of two-dimensional MXene materials is solved, and the effect of high specific surface area and large hydrogen storage capacity is achieved.

CN116216720BActive Publication Date: 2025-02-25SHENZHEN SENERGY FUEL CELL TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310253797.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-16
Publication Date
2025-02-25
Estimated Expiration
2043-03-16

AI Technical Summary

Technical Problem

In practical applications, the existing two-dimensional MXene materials have irreversible disorderly stacking due to the van der Waals force, resulting in significant loss of specific surface area, reduced exposed active sites, and reduced the intrinsic hydrogen storage capacity of the material.

Method used

By preparing a MXene aerogel for hydrogen storage, the preparation method includes reacting with LiF solution and Mn+1AXn solution to obtain MXene material, then dispersing it in water and adding a crosslinking agent, performing 3D printing and pretreatment , finally heat treatment is performed under an inert gas atmosphere to form an MXene aerogel with a three-dimensional structure.

Benefits of technology

The problem of hydrogen storage capacity decay caused by MXene material stacking is effectively solved. The prepared MXene aerogel has high specific surface area, large hydrogen storage capacity and excellent hydrogen absorption and discharge kinetics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application provides a MXene aerogel for hydrogen storage and a preparation method thereof, the method comprising: S01, adding LiF solution to MXene n+1 AX n The method comprises the following steps: step S02, dispersing the MXene material in water to obtain a MXene aqueous dispersion; adding a crosslinking agent to the MXene aqueous dispersion, stirring the dispersion evenly after ultrasonic treatment, and concentrating the dispersion to obtain ink; step S03, 3D printing the ink to obtain a MXene composite hydrogel; pretreating the MXene composite hydrogel to obtain a MXene composite aerogel; and heat-treating the MXene composite aerogel under an inert gas atmosphere to obtain a MXene aerogel having the advantages of high specific surface area and large hydrogen storage capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a MXene aerogel for hydrogen storage and a preparation method thereof. Background Art

[0002] Solid-state hydrogen storage has the advantages of safety, reliability, high storage efficiency and high volume density. It is currently the most promising hydrogen storage method. The principle of hydrogen storage is to store hydrogen in the material by adsorbing it on the surface of solid materials or by chemical reactions. The main solid hydrogen storage materials generally include alloy hydrogen storage materials, nano hydrogen storage materials, etc. Since the relative atomic mass of metals in alloy hydrogen storage materials is too large, the hydrogen storage mass density is generally less than 6wt%, which is difficult to meet the standards for on-board hydrogen storage.

[0003] MXene is a two-dimensional transition metal carbide, nitride or carbonitride, composed of a variety of different elements, with adjustable structure and performance. Its special layered structure and rich and complex surface functional groups enable it to physically adsorb, chemically adsorb and Kubas adsorb hydrogen. Its theoretical hydrogen storage capacity reaches 8.4wt%, showing broad development prospects in the field of hydrogen storage. However, like other two-dimensional materials, MXene nanosheets are irreversibly disordered and stacked under the influence of van der Waals forces, resulting in a significant loss of specific surface area, reducing the exposed active sites, and reducing the intrinsic hydrogen storage capacity of the material, thereby affecting the performance of the intrinsic performance of the material. Summary of the invention

[0004] Based on this, the embodiment of the present invention provides a MXene aerogel for hydrogen storage and a preparation method thereof, aiming to solve the problem that the existing two-dimensional MXene material sheets are driven by van der Waals forces, and irreversible disordered stacking occurs during actual application, resulting in significant loss of specific surface area, reduction of exposed active sites, and reduction of intrinsic hydrogen storage capacity of the material. The MXene aerogel prepared in this application has the advantages of high specific surface area, large hydrogen storage capacity, and excellent hydrogen absorption and desorption kinetics, and can effectively solve the problem of hydrogen storage capacity attenuation caused by MXene material stacking.

[0005] To achieve the above objectives, on the one hand, an embodiment of the present invention provides a method for preparing a MXene aerogel for hydrogen storage, comprising the following steps:

[0006] S01, add LiF solution to M n+1 AX n The solution is stirred evenly to obtain a mixed solution; the mixed solution is reacted at 35° C. to 60° C. for 24 h to 48 h to obtain a product; the product is pretreated to obtain a precipitate; the precipitate is dispersed in a solvent, and ultrasonically treated to obtain a MXene material (few-layer MXene). n+1 X n Tx type);

[0007] S02, dispersing the MXene material of step S01 in water to obtain a MXene aqueous dispersion; adding a crosslinking agent to the MXene aqueous dispersion, stirring evenly after ultrasonication, and concentrating to obtain ink; the mass ratio of the crosslinking agent to the MXene aqueous dispersion is 1:3 to 1:5;

[0008] S03, 3D printing the ink of step S02 to obtain a MXene composite hydrogel; pre-treating the MXene composite hydrogel to obtain a MXene composite aerogel; heat-treating the MXene composite aerogel at 400° C. to 600° C. for 4 h to 6 h under an inert gas atmosphere to obtain a MXene aerogel for hydrogen storage.

[0009] As a preferred embodiment, in step S01,

[0010] The LiF solution and the M n+1 AX n The volume ratio of the solution is 1:1.

[0011] The addition rate was 2 mL / min.

[0012] The LiF solution is a LiF hydrochloric acid solution, and each 50 mL of 12M hydrochloric acid solution contains 10 g of LiF.

[0013] The M n+1 AX n The solution is M n+1 AX n Hydrochloric acid solution, each 50mL of 12M hydrochloric acid solution contains 10gM n+1 AX n powder.

[0014] The M n+1 AX n The powder is a compound composed of transition metal, third group metal and carbon or nitrogen, wherein n is 1, 2 or 3.

[0015] The M n+1 AX n The powder is Ti3AlC2, Ti3AlN2, Nb3AlC2 or Mo3AlC2.

[0016] The pretreatment is vacuum filtration and washing until the pH value of the filtrate is 6-7, or centrifugal washing until the pH value of the filtrate is 6-7.

[0017] In each milliliter of the solvent, 5 mg to 15 mg of the precipitate is dispersed.

[0018] The solvent is water or ethanol.

[0019] The ultrasonic treatment time is 30 min to 60 min.

[0020] The MXene material is Ti3C2T x 、Ti3N2T x 、Nb3C2T x or Mo3C2T x etc. have the general chemical formula M n+1 X n T x Two-dimensional transition metal carbide or nitride (n is 1, 2, 3).

[0021] As a preferred embodiment, in step S02,

[0022] Each milliliter of the MXene aqueous dispersion contains 5 mg to 15 mg of MXene material.

[0023] The crosslinking agent is one or two of nano polystyrene microspheres, nano methyl methacrylate microspheres, ethylenediamine, polyacrylic acid, polyacrylamide, polyimide, polyvinyl alcohol and p-phenylenediamine.

[0024] The ultrasonic time is 30 min to 60 min.

[0025] The stirring time is 60 min to 120 min.

[0026] The ink is suitable for 3D printing, and each milliliter of the ink contains 40 mg to 60 mg of MXene material. The prepared ink has high apparent viscosity and non-Newtonian behavior of shear thinning, and can be used for 3D printing.

[0027] As a preferred embodiment, in step S03,

[0028] The printing temperature of the 3D printing is preferably 20°C to 25°C, the receiving panel temperature is preferably 4°C to 10°C, the printing layer thickness is 0.15mm / layer, the number of printing layers is 10 layers, the printing spacing is 1mm, and the printing speed is 10mm·s -1 .

[0029] The pretreatment method comprises freezing with liquid nitrogen for 24 hours and then freeze drying, the vacuum pressure of the freeze drying is 10Pa to 20Pa, and the freeze drying time is 48h to 72h.

[0030] The inert gas is nitrogen or argon.

[0031] On the other hand, an embodiment of the present invention also provides a MXene aerogel for hydrogen storage prepared by the above preparation method.

[0032] The present application can effectively solve the problem that the existing two-dimensional MXene material sheets are driven by van der Waals forces, and irreversible disordered stacking occurs during practical applications, resulting in significant loss of specific surface area, reduced exposed active sites, and reduced intrinsic hydrogen storage capacity of the material. The MXene aerogel prepared in the present application has the advantages of high specific surface area, large hydrogen storage capacity, and excellent hydrogen absorption and desorption kinetics, and can effectively solve the problem of hydrogen storage capacity attenuation caused by MXene material stacking. The preparation method of the present application is simple, low in preparation cost, short in preparation time, high in production efficiency, and easy to batch or large-scale production.

[0033] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the embodiments. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, top, bottom...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0036] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0037] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.

[0038] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0039] At present, like other two-dimensional materials, MXene nanosheets are irreversibly disordered and stacked under the influence of van der Waals forces, resulting in a significant loss of specific surface area, reducing the exposed active sites, and reducing the intrinsic hydrogen storage capacity of the material, thereby affecting the performance of the intrinsic performance of the material. Based on this, it is necessary to provide a MXene aerogel for hydrogen storage and a preparation method thereof to solve the above technical problems.

[0040] To achieve the above objectives, on the one hand, an embodiment of the present invention provides a method for preparing a MXene aerogel for hydrogen storage, comprising the following steps:

[0041] S01, add LiF solution to M n+1 AX n The solution is stirred evenly to obtain a mixed solution; the mixed solution is reacted at 35°C to 60°C (can be 35°C, 40°C, or 60°C, etc.) for 24h to 48h (can be 24h, 36h, or 48h, etc.) to obtain a product; the product is pretreated to obtain a precipitate; the precipitate is dispersed in a solvent, and ultrasonically treated to obtain a MXene material (few-layer MXene). n+1 X n T x type);

[0042] S02, dispersing the MXene material of step S01 in water to obtain a MXene aqueous dispersion; adding a crosslinking agent to the MXene aqueous dispersion, stirring evenly after ultrasonication, and concentrating to obtain ink; the mass ratio of the crosslinking agent to the MXene aqueous dispersion is 1:3 to 1:5;

[0043] S03. 3D printing the ink of step S02 to obtain a MXene composite hydrogel; pre-treating the MXene composite hydrogel to obtain a MXene composite aerogel; heat-treating the MXene composite aerogel at 400°C to 600°C (which may be 400°C, 500°C, or 600°C, etc.) under an inert gas atmosphere for 4h to 6h (which may be 4h, 5h, or 6h, etc.) to obtain a MXene aerogel (having a three-dimensional structure) for hydrogen storage.

[0044] As a preferred embodiment, in step S01,

[0045] The LiF solution and the M n+1 AX n The volume ratio of the solution is 1:1.

[0046] The addition rate was 2 mL / min.

[0047] The LiF solution is a LiF hydrochloric acid solution, and each 50 mL of 12M hydrochloric acid solution contains 10 g of LiF.

[0048] The M n+1 AX n The solution is M n+1 AX n Hydrochloric acid solution, each 50mL of 12M hydrochloric acid solution contains 10gM n+1 AX n powder.

[0049] The M n+1 AX n The powder is a compound composed of transition metal, third group metal and carbon or nitrogen, wherein n is 1, 2 or 3.

[0050] The M n+1 AX n The powder is Ti3AlC2, Ti3AlN2, Nb3AlC2 or Mo3AlC2.

[0051] The pretreatment is vacuum filtration and washing until the pH value of the filtrate is 6-7, or centrifugal washing until the pH value of the filtrate is 6-7.

[0052] In each milliliter of the solvent, 5 mg to 15 mg (5 mg, 10 mg, or 15 mg, etc.) of the precipitate is dispersed.

[0053] The solvent is water or ethanol.

[0054] The ultrasonic treatment time is 30 min to 60 min (may be 30 min, 40 min, or 60 min, etc.).

[0055] The MXene material is Ti3C2T x 、Ti3N2T x 、Nb3C2T x or Mo3C2T x etc. have the general chemical formula M n+1 X n T x (n is 1, 2, 3; X represents the amount of functional groups, the value of X is related to the etching conditions, and the value of X is different under different etching conditions.) Two-dimensional transition metal carbide or nitride.

[0056] As a preferred embodiment, in step S02,

[0057] Each milliliter of the MXene aqueous dispersion contains 5 mg to 15 mg (which may be 5 mg, 10 mg, or 15 mg, etc.) of MXene material.

[0058] The crosslinking agent is one or two of nano polystyrene microspheres, nano methyl methacrylate microspheres, ethylenediamine, polyacrylic acid, polyacrylamide, polyimide, polyvinyl alcohol and p-phenylenediamine.

[0059] The ultrasonic time is 30 min to 60 min (can be 30 min, 40 min, or 60 min, etc.).

[0060] The stirring time is 60 min to 120 min (may be 60 min, 90 min, or 120 min, etc.).

[0061] The ink is suitable for 3D printing, and each milliliter of the ink contains 40 mg to 60 mg of MXene material. The prepared ink has high apparent viscosity and non-Newtonian behavior of shear thinning, and can be used for 3D printing.

[0062] As a preferred embodiment, in step S03,

[0063] The printing temperature of the 3D printing is preferably 20°C to 25°C (can be 20°C, 22°C, or 25°C, etc.), the receiving panel temperature is preferably 4°C to 10°C (can be 4°C, 8°C, or 10°C, etc.), the printing layer thickness is 0.15mm / layer, the number of printing layers is 10 layers, the printing spacing is 1mm, and the printing speed is 10mm·s -1 .

[0064] The pretreatment method is to freeze with liquid nitrogen for 24 hours and then freeze-dry. The vacuum pressure of the freeze-drying is 10Pa~20Pa (can be 10Pa, 15Pa, or 20Pa, etc.), and the freeze-drying time is 48h~72h (can be 48h, 56h, or 72h, etc.).

[0065] The inert gas is nitrogen or argon.

[0066] On the other hand, an embodiment of the present invention also provides a MXene aerogel for hydrogen storage prepared by the above preparation method.

[0067] The MXene aerogel prepared in the present application has a three-dimensional structure, which can fully transfer the properties of two-dimensional materials to the macroscopic level, while taking into account the characteristics of the three-dimensional structure such as large specific surface area, specific pore environment, and strong adsorption performance. It can effectively reduce the irreversible agglomeration and stacking phenomena caused by van der Waals forces, which can not only retain the active sites of MXene, but also facilitate the construction of an interconnected hierarchical pore structure.

[0068] The present application can effectively solve the problem that the existing two-dimensional MXene material sheets are driven by van der Waals forces, and irreversible disordered stacking occurs during practical applications, resulting in significant loss of specific surface area, reduced exposed active sites, and reduced intrinsic hydrogen storage capacity of the material. The MXene aerogel prepared in the present application has the advantages of high specific surface area, large hydrogen storage capacity, and excellent hydrogen absorption and desorption kinetics, and can effectively solve the problem of hydrogen storage capacity attenuation caused by MXene material stacking. The preparation method of the present application is simple, low in preparation cost, short in preparation time, high in production efficiency, and easy to batch or large-scale production.

[0069] Example 1

[0070] A method for preparing MXene aerogel for hydrogen storage comprises the following steps:

[0071] S01, add LiF solution to M n+1 AX n The solution was stirred evenly to obtain a mixed solution; the mixed solution was reacted at 40° C. for 48 hours to obtain a product; the product was pretreated to obtain a precipitate; the precipitate was dispersed in a solvent, and ultrasonic treatment was performed to obtain a MXene material (few-layer MXene) n+1 X n T x type);

[0072] S02, dispersing the MXene material of step S01 in water to obtain a MXene aqueous dispersion; adding a crosslinking agent to the MXene aqueous dispersion, stirring evenly after ultrasonication, and concentrating to obtain ink; the mass ratio of the crosslinking agent to the MXene aqueous dispersion is 1:4;

[0073] S03. 3D printing the ink of step S02 to obtain a MXene composite hydrogel; pre-treating the MXene composite hydrogel to obtain a MXene composite aerogel; and heat-treating the MXene composite aerogel at 400° C. for 4 hours under an inert gas atmosphere to obtain a MXene aerogel (having a three-dimensional structure) for hydrogen storage.

[0074] In step S01,

[0075] The LiF solution and the M n+1 AX n The volume ratio of the solution is 1:1.

[0076] The addition rate was 2 mL / min.

[0077] The LiF solution is a LiF hydrochloric acid solution, and each 50 mL of 12M hydrochloric acid solution contains 10 g of LiF.

[0078] The M n+1 AX n The solution is M n+1 AX n Hydrochloric acid solution, each 50mL of 12M hydrochloric acid solution contains 10gM n+1 AX n powder.

[0079] The M n+1 AX n The powder is Ti3AlC2.

[0080] The pretreatment is vacuum filtration and washing until the pH value of the filtrate is 6-7.

[0081] 10 mg of the precipitate was dispersed in each ml of the solvent.

[0082] The solvent is water. The ultrasonic treatment time is 60 min. The MXene material is Ti3C2T x .

[0083] In step S02,

[0084] Each milliliter of the MXene aqueous dispersion contains 10 mg of MXene material.

[0085] The cross-linking agent is polyacrylic acid. The ultrasonication time is 60 min. The stirring time is 60 min.

[0086] The ink is suitable for 3D printing, and each milliliter of the ink contains 50 mg of MXene material. The ink is a homogeneous ink, and the crossover point value between the storage modulus (G′) and the loss modulus (G″) is 324 Pa, and the ink processability parameter G′ / G″ ratio is about 7.4.

[0087] In step S03,

[0088] The printing temperature of the 3D printing is 20°C, the receiving panel temperature is 10°C, the printing layer thickness is 0.15mm / layer, the number of printing layers is 10 layers, the printing spacing is 1mm, and the printing speed is 10mm·s -1 .

[0089] The pretreatment method is to freeze with liquid nitrogen for 24 hours and then freeze-dry, the vacuum pressure of the freeze-drying is 10Pa, and the freeze-drying time is 48 hours. The inert gas is nitrogen.

[0090] The BET specific surface area of ​​MXene aerogel reaches 168m 2 / g. At 25°C and 50 bar hydrogen pressure, the hydrogen absorption capacity of MXene aerogel reaches 6.5wt%, and at 100°C and 0.5 bar hydrogen pressure, the hydrogen release capacity reaches 81% within one minute.

[0091] Example 2

[0092] A method for preparing MXene aerogel for hydrogen storage comprises the following steps:

[0093] S01, add LiF solution to M n+1 AX n The solution was stirred evenly to obtain a mixed solution; the mixed solution was reacted at 40° C. for 48 hours to obtain a product; the product was pretreated to obtain a precipitate; the precipitate was dispersed in a solvent, and ultrasonic treatment was performed to obtain a MXene material (few-layer MXene) n+1 X n T x type);

[0094] S02, dispersing the MXene material of step S01 in water to obtain a MXene aqueous dispersion; adding a crosslinking agent to the MXene aqueous dispersion, stirring evenly after ultrasonication, and concentrating to obtain ink; the mass ratio of the crosslinking agent to the MXene aqueous dispersion is 1:3;

[0095] S03. 3D printing the ink of step S02 to obtain a MXene composite hydrogel; pre-treating the MXene composite hydrogel to obtain a MXene composite aerogel; and heat-treating the MXene composite aerogel at 500° C. for 4 hours under an inert gas atmosphere to obtain a MXene aerogel (having a three-dimensional structure) for hydrogen storage.

[0096] In step S01,

[0097] The LiF solution and the M n+1 AX n The volume ratio of the solution is 1:1.

[0098] The addition rate was 2 mL / min.

[0099] The LiF solution is a LiF hydrochloric acid solution, and each 50 mL of 12M hydrochloric acid solution contains 10 g of LiF.

[0100] The M n+1 AX n The solution is M n+1 AX n Hydrochloric acid solution, each 50mL of 12M hydrochloric acid solution contains 10gM n+1 AX n powder.

[0101] The M n+1 AX n The powder is Ti3AlN2.

[0102] The pretreatment is centrifugal washing until the pH of the filtrate is 6-7.

[0103] 10 mg of the precipitate was dispersed in each ml of the solvent.

[0104] The solvent is ethanol.

[0105] The ultrasonic treatment time is 60 min.

[0106] The MXene material is Ti3N2T x .

[0107] In step S02,

[0108] Each milliliter of the MXene aqueous dispersion contains 10 mg of MXene material.

[0109] The cross-linking agent is nano polystyrene microspheres.

[0110] The ultrasonic time is 60 min.

[0111] The stirring time is 60 min.

[0112] The ink is suitable for 3D printing, and each milliliter of the ink contains 40 mg of MXene material. The ink is a homogeneous ink, and the crossover point value between the storage modulus (G′) and the loss modulus (G″) is 218 Pa, and the ink processability parameter G′ / G″ ratio is about 7.2.

[0113] In step S03,

[0114] The printing temperature of the 3D printing is 20°C, the receiving panel temperature is 4°C, the printing layer thickness is 0.15mm / layer, the number of printing layers is 10 layers, the printing spacing is 1mm, and the printing speed is 10mm·s -1 .

[0115] The pretreatment method is to freeze with liquid nitrogen for 24 hours and then freeze-dry. The vacuum pressure of the freeze-drying is 10Pa and the freeze-drying time is 48 hours.

[0116] The inert gas is nitrogen.

[0117] The BET specific surface area of ​​the prepared MXene aerogel reaches 147 m 2 / g. At 25°C and 50 bar hydrogen pressure, the hydrogen absorption capacity of MXene aerogel reaches 6.2wt%, and at 100°C and 0.5 bar hydrogen pressure, the hydrogen release capacity reaches 85% within one minute.

[0118] Example 3

[0119] A method for preparing MXene aerogel for hydrogen storage comprises the following steps:

[0120] S01, add LiF solution to M n+1 AX n The solution was stirred evenly to obtain a mixed solution; the mixed solution was reacted at 40° C. for 48 hours to obtain a product; the product was pretreated to obtain a precipitate; the precipitate was dispersed in a solvent, and ultrasonic treatment was performed to obtain a MXene material (few-layer MXene) n+1 X n T x type);

[0121] S02, dispersing the MXene material of step S01 in water to obtain a MXene aqueous dispersion; adding a crosslinking agent to the MXene aqueous dispersion, stirring evenly after ultrasonication, and concentrating to obtain ink; the mass ratio of the crosslinking agent to the MXene aqueous dispersion is 1:5;

[0122] S03. 3D printing the ink of step S02 to obtain a MXene composite hydrogel; pre-treating the MXene composite hydrogel to obtain a MXene composite aerogel; and heat-treating the MXene composite aerogel at 600° C. for 6 hours under an inert gas atmosphere to obtain a MXene aerogel (having a three-dimensional structure) for hydrogen storage.

[0123] In step S01,

[0124] The LiF solution and the M n+1 AX n The volume ratio of the solution is 1:1.

[0125] The addition rate was 2 mL / min.

[0126] The LiF solution is a LiF hydrochloric acid solution, and each 50 mL of 12M hydrochloric acid solution contains 10 g of LiF.

[0127] The M n+1 AX n The solution is M n+1 AX n Hydrochloric acid solution, each 50mL of 12M hydrochloric acid solution contains 10gM n+1 AX n powder.

[0128] The M n+1 AX n The powder is Ti3AlC2.

[0129] The pretreatment is vacuum filtration and washing until the pH value of the filtrate is 6-7.

[0130] 10 mg of the precipitate was dispersed in each ml of the solvent.

[0131] The solvent is water.

[0132] The ultrasonic treatment time is 60 min.

[0133] The MXene material is Ti3C2T x .

[0134] In step S02,

[0135] Each milliliter of the MXene aqueous dispersion contains 10 mg of MXene material.

[0136] The cross-linking agent is p-phenylenediamine.

[0137] The ultrasonic time is 60 min.

[0138] The stirring time is 60 min.

[0139] The ink is suitable for 3D printing, and each milliliter of the ink contains 50 mg of MXene material. The ink is a homogeneous ink, and the crossover value between the storage modulus (G′) and the loss modulus (G″) is 569 Pa, and the ink processability parameter G′ / G″ ratio is about 11.2.

[0140] In step S03,

[0141] The printing temperature of the 3D printing is 20°C, the receiving panel temperature is 10°C, the printing layer thickness is 0.15mm / layer, the number of printing layers is 10 layers, the printing spacing is 1mm, and the printing speed is 10mm·s -1 .

[0142] The pretreatment method is to freeze with liquid nitrogen for 24 hours and then freeze-dry. The vacuum pressure of the freeze-drying is 10Pa and the freeze-drying time is 48 hours.

[0143] The inert gas is nitrogen.

[0144] The BET specific surface area of ​​the prepared MXene aerogel reaches 185 m 2 / g. At 25°C and 50 bar hydrogen pressure, the hydrogen absorption capacity of MXene aerogel reaches 6.8wt%, and at 100°C and 0.5 bar hydrogen pressure, the hydrogen release capacity reaches 83% within one minute.

[0145] Comparative Example 1

[0146] A method for preparing MXene aerogel for hydrogen storage comprises the following steps:

[0147] Add LiF solution to M n+1 AX n The solution is stirred evenly to obtain a mixed solution; the mixed solution is reacted at 35° C. to 60° C. for 24 h to 48 h to obtain a product; the product is pretreated to obtain a precipitate; the precipitate is dispersed in a solvent, and ultrasonically treated to obtain a MXene material (few-layer MXene). n+1 X n T x type);

[0148] in,

[0149] The LiF solution and the M n+1 AX n The volume ratio of the solution is 1:1.

[0150] The addition rate was 2 mL / min.

[0151] The LiF solution is a LiF hydrochloric acid solution, and each 50 mL of 12M hydrochloric acid solution contains 10 g of LiF.

[0152] The M n+1 AX n The solution is M n+1 AX n Hydrochloric acid solution, each 50mL of 12M hydrochloric acid solution contains 10gM n+1 AX n powder.

[0153] The M n+1 AX n The powder is Ti3AlC2.

[0154] The pretreatment is vacuum filtration and washing until the pH value of the filtrate is 6-7.

[0155] 10 mg of the precipitate was dispersed in each ml of the solvent.

[0156] The solvent is water.

[0157] The ultrasonic treatment time is 60 min.

[0158] The MXene material is Ti3C2T x .

[0159] The BET specific surface area of ​​the prepared two-dimensional MXene aerogel reaches 45 m 2 / g. At 25°C and 50 bar hydrogen pressure, the hydrogen absorption capacity of MXene aerogel reaches 5.4wt%, and at 100°C and 0.5 bar hydrogen pressure, the hydrogen release capacity reaches 87% within one minute.

[0160] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing MXene aerogel for hydrogen storage, characterized in that: The steps include: S01, add LiF solution to M n+1 AX n The solution is stirred evenly to obtain a mixed solution; the mixed solution is reacted at 35° C. to 60° C. for 24 h to 48 h to obtain a product; Pre-treating the product to obtain a precipitate; dispersing the precipitate in a solvent and ultrasonically treating the precipitate to obtain a MXene material; S02, dispersing the MXene material of step S01 in water to obtain a MXene aqueous dispersion; adding a crosslinking agent to the MXene aqueous dispersion, stirring evenly after ultrasonic treatment, and concentrating to obtain ink; the mass ratio of the crosslinking agent to the MXene aqueous dispersion is 1:3 to 1:5; S03, 3D printing the ink of step S02 to obtain a MXene composite hydrogel; pre-treating the MXene composite hydrogel to obtain a MXene composite aerogel; heat-treating the MXene composite aerogel at 400° C. to 600° C. for 4 h to 6 h under an inert atmosphere to obtain a MXene aerogel for hydrogen storage; In step S01, the M n+1 AX n The powder is Ti3AlC2 or Ti3AlN2; The MXene material is Ti3C2T x or Ti3N2T x ; The cross-linking agent is one or two of nano polystyrene microspheres, nano methyl methacrylate microspheres, ethylenediamine, polyacrylic acid, polyacrylamide, polyimide, polyvinyl alcohol and p-phenylenediamine; The ink is an ink suitable for 3D printing, and each milliliter of the ink contains 40 mg to 60 mg of the MXene material; In step S03, the printing temperature of the 3D printing is 20℃~25℃, the receiving panel temperature is 4℃~10℃, the printing layer thickness is 0.15mm / layer, the number of printing layers is 10 layers, the printing spacing is 1mm, and the printing speed is 10mm•s -1 ; The pretreatment method comprises freezing with liquid nitrogen for 24 hours and then freeze drying, the vacuum pressure of the freeze drying is 10Pa to 20Pa, and the freeze drying time is 48h to 72h.

2. The method for preparing MXene aerogel for hydrogen storage according to claim 1, characterized in that: In step S01, the LiF solution and the M n+1 AX n The volume ratio of the solution is 1:1; the addition rate is 2 mL / min; The LiF solution is a LiF hydrochloric acid solution, and each 50 mL of 12M hydrochloric acid solution contains 10 g of LiF; The M n+1 AX n The solution is M n+1 AX n Hydrochloric acid solution, each 50mL of 12M hydrochloric acid solution contains 10g M n+1 AX n powder.

3. The method for preparing MXene aerogel for hydrogen storage according to claim 1, characterized in that: In step S01, the pretreatment is vacuum filtration and washing until the pH value of the filtrate is 6 to 7, or centrifugal washing until the pH value of the filtrate is 6 to 7; Dispersing 5 mg to 15 mg of the precipitate in each milliliter of the solvent; The solvent is water or ethanol; the ultrasonic treatment time is 30 min to 60 min.

4. The method for preparing MXene aerogel for hydrogen storage according to claim 3, characterized in that: In step S02, each milliliter of the MXene aqueous dispersion contains 5 mg to 15 mg of the MXene material.

5. The method for preparing MXene aerogel for hydrogen storage according to claim 4, characterized in that: In step S02, the ultrasonication time is 30 min to 60 min; the stirring time is 60 min to 120 min.

6. The method for preparing MXene aerogel for hydrogen storage according to claim 1, characterized in that: In step S03, The inert atmosphere is nitrogen or argon.

7. A MXene aerogel for hydrogen storage, characterized in that: The method is prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Two-dimensional transition metal carbide (nitride) aerogel as well as preparation method and application thereof

    CN109437202A